A Defect in Collagen Receptor-Ca2+ Signaling System in Platelets from Cattle with Chediak-Higashi Syndrome - Shiraishi, Mitsuya; Kawashima, Sachiko; Moroi, Masaaki; Shin, Yangchol; Morita, Takashi; Horii, Yoichiro; Ikeda, Masahiro; Ito, Katsuaki (Thrombosis and Haemostasis, 2002)
Decreased platelet aggregation to collagen is a cause for bleeding diathesis of Chediak-Higashi syndrome (CHS). We investigated whether the collagen receptor-Ca2+ signaling system was impaired in platelets from cattle affected with CHS. A collagen-induced increase in cytosolic Ca2+ ([Ca2+]i) was depressed in CHS platelets, which was accompanied by a decrease in the production of inositol 1,4,5-trisphosphate. When the influences of endogenous arachidonic acid metabolites and ADP were excluded, convulxin or collagen-related peptide, which are specific agonists for the collagen receptor GPVI, increased [Ca2+]i in both normal and CHS platelets. In contrast, rhodocytin, which was thought to activate another collagen receptor GPIa/IIa, increased [Ca2+]i in CHS platelets to a lesser extent than in normal ones. Cytochalasin D, an actin polymerization inhibitor, depressed the response to collagen or rhodocytin but not the response to convulxin. Adhesion of CHS platelets to acid soluble type I collagen, which was mediated by GPIa/IIa, was similar to that of normal platelets. These results suggest that a defect in the rhodocytin-sensitive pathway is responsible for decreasing the response to collagen in CHS platelets. It remains to be determined which receptor is associated with the mechanism.
Keywords: Chediak-Higashi syndrome; bovine platelet; Ca2+ mobilization; collagen receptor; rhodocytin